The Role of colleges of Education in enhancing the intellectual security of Students - أحمد مطيعة; جديد لبنى (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to know the role of the College of Education in enhancing the intellectual security of students, by identifying the role of faculty members and college administration in enhancing their intellectual security. The research also aimed to identify the most prominent obstacles that prevent the college from playing its role effectively in enhancing intellectual security. The study tool is a questionnaire directed to members of the teaching staff at the College of Education at Tishreen University, which represented the study sample and consisted of 54 members, an educational body. The study found that the role of faculty members in enhancing students’ intellectual security was high. While the college administration played a mediating role. The most prominent of the obstacles was the weak assessment of the seriousness of intellectual security. The study suggested including security issues in university curricula and activating intellectual security encounters with students.